Vegetable varieties/hybrids from IIVR, Varanasi - Singh, B.; Singh, Major; Lal, H.; Rai, N.; Bhardwaj, D. R.; Kumar, Rajesh; Pandey, Sudhakar; Prasanna, H. C.; Chaubey, T.; Sanwal, S. K.; Tiwari, S. K.; Singh, P. M. (Indian Horticulture, 2019)
The major objectives of breeding are to develop the varieties with earliness, good horticultural characters and resistance to diseases. The price of vegetables is directly correlated with the availability of good quality produce in the market. Farmers are always trying to get the produce earliest from their farms to earn more profit due to short supply of that vegetable to reach the market before main season of crop. Institute has developed many varieties of different maturity groups having resistance to many diseases. Adoption of these varieties may be profitable to the farmers with small land holding.